P258 Infant lung function testing: a new approach using a rapid, portable system for measuring lung clearance index (LCI) in health and disease. (15th November 2016) - Shawcross, A; Murray, CS; Kirkby, J; Miles, J; Pike, K; Rees, S; Aurora, P; Horsley, A
Abstract : Introduction: Lung clearance index (LCI) is a sensitive measure of lung disease in infants, with potential applications in clinical practice and research. However, measuring LCI in infants is technically challenging and there is no simple method of assessing LCI outside of specialist research laboratories in this population. We have previously described an alternative method of measuring LCI, in which expired gas is collected and analysed to derive functional residual capacity (FRC) and LCI without directly measuring flow. This eliminates one of the major technical challenges, whilst also reducing the system's dead space. This method is highly accurate in vitro, with a mean accuracy of FRC measurement to within 1%, down to FRC of 100ml. 1 The method does not require large external gas tanks, and washout is performed breathing room air, making the system fully portable. Aim: To assess the performance of this method in vivo. Method: Healthy controls and infants with CF are currently being recruited to undergo LCI measurement using this method. Practical applicability of the system is determined by the number of successful tests and within-subject repeatability, defined as coefficient of variation (CV%) of same-visit repeats. Comparison will be made with LCI measurements obtained using a respiratory mass spectrometer, currently considered the gold standard for infant LCI measurement. Results: To date, 10 healthy controls (mean age 53 weeks) and 2 infants with CF (mean age 55 weeks) have successfully undergone LCI measurement using this method. Mean LCI in controls was 6.62 (range 5.79–7.91). Mean within-subject CV% was 5.9%. Mean LCI in infants with CF was 7.63 (CV 5%). Conclusion: Preliminary data suggest this is a feasible and reproducible method of performing LCI in infants. Results in both infants with CF and controls fall within ranges predicted by the respiratory mass spectrometer 2 and within accuracy limits set by international guidelines. This could provide a more accessible alternative to current technologies, enabling this test to be offered in more centres. References: Shawcross, et al . Ped Pulmonol 2016;51 :491–497. Lum, et al . Eur Respir J 2013;41 :1371–7.